Mangrove bark tannins as a Zn–P coating sealant for mild steel corrosion protection in 3.5% NaCl solution - Shahadad Zainol Abidin; M Hazwan Hussin (Materials Research Express, 2020)
In this work, mangrove bark tannins have been studied as a sealant after Zn–P of mild steel. The efficiency of the sealant against the corrosion was tested by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarisation (PD) in 3.5% NaCl solution. The increased in the concentration of the tannin as a sealant increases the inhibition efficiency up to optimum concentration of 4 g l ^−1 . The inhibition efficiencies of tannin methanol extract (TME) and 70% tannin acetone extract (TAE) were 83.52% and 71.12% respectively. The results obtained from EIS and PD were in a good agreement and complementary to each other. The double layer constant phase element capacitance (CPE _dl ) decrease indicated that a film form on the surface of the mild steel that retard the corrosion activities. Further, the pore modifications and elemental compositions were analyzed by scanning electron microscope (SEM) and energy dispersive x-ray (EDX).